Studi Deskriptif Implementasi Pembelajaran Daring melalui Learning Management System di Pusat Pengembangan Sumber Daya Manusia Minyak dan Gas Bumi - Mohammad Hasan Syukur (Pusat Pengembangan Sumber Daya Manusia Minyak dan Gas Bumi, 2021)
The Covid-19 pandemic era has disrupted the conventional learning process. Online learning is one alternative that can solve this problem. An alternative solution is needed to answer these problems. The research objective was to obtain an overview of the implementation of online learning at PPSDM MIGAS. The research methodology carried out is by surveying through a questionnaire with google form which is distributed to stake holders of training organizers and teachers (lecturers and instructors). From the research results obtained data that 97.6% stated that PPSDM MIGAS carried out online learning, 95.1% stated that learning from was a combination of video conferencing and LMS, 82.9% were able to organize online learning, 95.1% were more pleased with zoom than the platform other, 80.5% prefer group Whatsapp as asynchronous in online learning, 22% receive bandwidth below 10 Mbps. Overall these results state that PPSDM MIGAS Stakeholders are ready to carry out online learning but still need human resource development both in LMS management and in interested presentation materials and learning media likes videos, simulation etc.